OC-083 Clinical trial: influence of bovine colostrum on intestinal permeability in healthy athletes after heavy exercise. (23rd September 2015) - Marchbank, T; Davison, G; Oakes, J R; Ghatei, M; Patterson, M; Rolfs, J; Playford, R J
Abstract : Introduction: Heavy exercise results in gut symptoms and in extreme cases "heat stroke" due, in part, to increased intestinal permeability of luminal toxins. We examined if bovine colostrum a rich source of growth factors and immune modulators could prevent these permeability changes. Methods: Twelve healthy volunteers completed a double-blind, placebo-controlled, crossover protocol (14 days colostrum or placebo) prior to standardised exercise. Gut permeability utilised 5 h urinary lactulose: rhamnose ratios. In vitro studies (T84 cells) examined effects of colostrum on temperature-induced apoptosis (active caspase-3) and epithelial resistance. Results: For both arms of study, exercise increased the blood lactate, heart rate, core temperature (mean 2°C rise) and plasma VIP by similar amounts. However, GLP-1 plasma levels results were discordant; rising by 88.7 pmol/l in placebo arm but falling by 4.2 pmol/l in colostrum arm (p=0.026). Intestinal permeability in placebo arm increased 2.5-fold following exercise (0.38±0.012 baseline value, to 0.92±0.014, p<0.01), whereas colostrum truncated this rise by 80% (only rising from 0.38±0.012, initial baseline value, to 0.49±0.017) following exercise. In vitro apoptosis increased by 63% in response to increasing temperature by 2°C whereas this effect was truncated by 66% if colostrum was co-present (all p<0.01). Similar results were obtained when changes in epithelial resistance were assessed (colostrum truncating the fall in resistance by 64%, p<0.01). Conclusion: Bovine colostrum reduced exercise-induced increase in gut permeability, possibly through mechanisms including reducing temperature-induced apoptosis. This may have value in enhancing athletic performance and preventing heat stroke.